Perceptions of health: (dis)integration and (mis)integration of refugees in Nairobi, Kenya - Boeyink, Clayton; Metobo, Brenda; Wanga, Myriam; Mastaki, Pascal; Atambo, Lydia (Frontiers in Human Dynamics, 2024)
This article utilizes 40 in-depth interviews of healthcare workers (HCWs) including Kenyan nurses, medical doctors, psychologists, pharmacists, refugee NGO officers, and others based in Nairobi who come in professional contact with Congolese and Somali refugees on a regular basis. They were asked to describe barriers to healthcare, care seeking behaviors, and pathways to care that refugees experience. These responses are juxtaposed with 60 life-history interviews exploring the same topics with Congolese and Somali refugees living in Kawangware and Eastleigh estates. In short, this article argues that refugees and HCWs have a shared understanding of the barriers to healthcare for displaced people such as poverty, refugee documentation issues, and inadequacy of Nairobi's healthcare system for marginalized populations. However, there is a significant disconnect in perspectives for how healthcare integration should take place regarding major causes of ill health such as malnutrition and poor hygiene. Refugees understand oppression as a primary structural determinant of health, whereas many HCWs take an individualized view, advocating for modifications of knowledge and behaviors of refugees rather than adjusting structural issues. This is reflective of larger processes whereby refugees are actively "(dis)integrated" by state and society and are seen by many Kenyans as "(mis)integrating)", or integrating "wrongly" or "badly", which has major implications for how to shape possible policy interventions.